Evaluation of Temperature Distribution on Human Skin During Philaser Tattoo Removal - Salman, Zahra Amer; Al-dahan, Ziad Tarik; Al-Hamaoy, Ahmed (Al-Nahrain Journal for Engineering Sciences, 2025)
Many difficulties were recorded during laser-assisted tattoo removal. But most of them remain unknown. The recent literatures on laser tattoo removal focuses more on removal methods and systems than on side effects, such as temperature increase over tissue and ideal treatment parameters. This study aims to assess the surface temperature in compliance with eyebrow tattoo removal. The study was carried out for 55 patients aged between 22 and 43 years. The treatment was performed using a Nd:YAG laser (1064nm, Phi laser system) with an energy of 1000 mJ, a frequency of 3Hz, and a spot size of 8mm. The surface temperature of the skin during tattoo removal process was measured with a FLIR thermal camera. The results were analyzed by testing the normal state of distribution. The Shapiro-Wilk and Kolmogorov-Smirnov tests were used. All patients finished the full treatment of three laser sessions to achieve the goal of total removal. After temperature comparison, the results showed a significant influence of skin nature and patients’ age on temperature distribution on skin, as for older patients, the energy absorption increased. Additionally, patients with darker skin tones exhibited greater absorption. The benefit of deepening understanding appeared in the Temperature distribution in the tissues of the affected area and the surrounding area during laser irradiation, as it provides a guiding and reference function for the effect of photothermal therapy.